2021
DOI: 10.1088/1748-3190/ac2e0c
|View full text |Cite
|
Sign up to set email alerts
|

Mem-fractive properties of mushrooms

Abstract: Memristors close the loop for I–V characteristics of the traditional, passive, semi-conductor devices. A memristor is a physical realisation of the material implication and thus is a universal logical element. Memristors are getting particular interest in the field of bioelectronics. Electrical properties of living substrates are not binary and there is nearly a continuous transitions from being non-memristive to mem-fractive (exhibiting a combination of passive memory) to ideally memristive. In laboratory exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…[179,180] This could permit the design of mycelium composites for optical, tactile, and chemical sensors; storage devices; signal processors, and decision-making tools. [181] Adamatzky [182] has suggested that mycelium decision-making tools could convert environmental stimuli received through the fruiting body into electrical signals and the computation would be conducted within the mycelium network itself. There is also an interest to use mycelium for the next-generation of monolithic buildings that can self-grow and self-repair using natural environmental adaptation mechanisms.…”
Section: E-waste Managementmentioning
confidence: 99%
“…[179,180] This could permit the design of mycelium composites for optical, tactile, and chemical sensors; storage devices; signal processors, and decision-making tools. [181] Adamatzky [182] has suggested that mycelium decision-making tools could convert environmental stimuli received through the fruiting body into electrical signals and the computation would be conducted within the mycelium network itself. There is also an interest to use mycelium for the next-generation of monolithic buildings that can self-grow and self-repair using natural environmental adaptation mechanisms.…”
Section: E-waste Managementmentioning
confidence: 99%
“…Second, we can prototype neuromorphic circuits with kombucha mats. There is a high likelihood of kombucha mats exhibiting memristive properties (similar to memristive properties of slime mould [51] and fungi [52]). The memristive properties would further imply [53, 54, 55, 56] that it is possible to implement learning, memory and construct synaptic connections in the zoogleal mats.…”
Section: Discussionmentioning
confidence: 99%
“…135 They determined the intact leaf material to be a non-ideal memristor with good retention and fast switching. Memristive properties have even been found in grey oyster mushrooms 136 using electrodes directly implanted in their fruiting bodies.…”
Section: Intact Biological Tissuementioning
confidence: 99%